Ecological Education Through Folklore Hikayat Pak and Mak Siti From South Sumatra - Hidajati, Enny; Saputri, Kurnia (PPSDP International Journal of Education, 2023)
The purpose of this study is to examine how the ecological elements in the folklore Hikayat Pak and Mak Siti and what meaning can students learn from this folk tale. The method used in this research is descriptive qualitative with analytical method through objective approach. While the approach used is an interdisciplinary approach because it analyzes the contents of the story by using other theories such as ecocritical and folklore theories. The results obtained in this folklore contain four things related to eco-criticism, namely elements of wilderness, places to live, animals, and the earth. Meanwhile, ecological messages that can be conveyed to students are: (a) maintaining forest sustainability as part of an ecosystem which is important for life. (b) protecting animals and looking after animals that are almost extinct, such as tigers. (c) caring for God’s fellow creatures, such as plants, animals, water, air and others. (d) maintaining cleanliness, order, and the beauty of the environment for the sake of mutual comfort. Meanwhile, from the message of this story, it can be concluded that students have several attitudes, namely (a) being consistent in the truth, honest, trustworthy, and can be trusted by others, (b) may not be detrimental to others for personal gain, (c) even though children have more control over technology, parents must still accompany their children, (d) students must prepare themselves with various knowledge and skills to become leaders in the future, (e) must not be arrogant and must continue to want to learn from the surrounding environment, (f) Religious leaders must be sincere and willing to guide their people towards goodness.